PS5:95 Circulating angiogenic t-cells are reduced in patients with systemic lupus erythematosus with high disease activity and without known cardiovascular risk factors. (21st March 2018) - Piantoni, S; Cavazzana, I; Fredi, M; Taraborelli, M; Franceschini, F; Tincani, A; Airo', P
Abstract : Background: Recent evidences underlined the central role of T-cells in the pathogenesis of Systemic Lupus Erythematosus (SLE) and in its cardiovascular complications. 1 CD3 +CD31+CXCR4+angiogenic T-cells (Tang) have been identified as a T-cell subtype involved in the repair of damaged endothelium cooperating with endothelial progenitor cells. 2 Tang were described as selectively expanded in the circulation of systemic sclerosis patients displaying peripheral vascular complications, as a reaction to an inefficient angiogenesis. 3 Not much information is available on Tang in a SLE patients: in a recent study the percentage of circulating CD8 +Tang, but not CD4 +Tang, was higher in SLE than in healthy controls. 4 However, in this study SLE patients with hypertension, dyslipidemia or smoking habit, factors which may influence Tang counts, were not excluded. The aim of this study was to characterise Tang in a cohort of patients with SLE without known cardiovascular risk factors. Methods: Twenty female SLE patients with a recent disease onset (<5 years) and without traditional cardiovascular risk factors or previous events (age: median value=43 [25th-75th percentile=27–54] years) and 18 healthy controls (age: 40 [32–54] years) were enrolled. Phenotypic analysis of peripheral Tang lymphocytes was made by flow-cytometry. Disease activity was evaluated by SLEDAI-2K score. Results: SLE patients were divided in two groups according with disease activity. Patients with SLEDAI-2K equal or higher than 6 were defined as patients with high disease activity (n:5). They had a lower percentage of circulating Tang in comparison with healthy controls (10 [8–15] vs 16 [14–23]% of CD3 +T cells, p=0.04). The result was confirmed in absolute number (83 [60–103] vs 242 [165–328] cell/microliter, p=0.04). SLE patients with low disease activity had levels of Tang which were intermediate between, and not significantly different from, healthy controls and patients with high disease activity. Conclusions: Tang were reduced in our patients with active SLE, and no known cardiovascular risk factors, suggesting that this reduction was directly explained by disease activity. References: . Mak A. J Immunol Res 2014. . Hur J. Circulation2007. . Manetti M. PLoS One2017. . Miao J. Mediators Inflamm2016.